Anatomical feasibility of a new off-the-shelf inner branch stent graft (E-nside) for endovascular treatment of thoraco-abdominal aneurysms. (15th October 2020) - Bilman, Victor; Cambiaghi, Tommaso; Grandi, Alessandro; Carta, Niccolò; Melissano, Germano; Chiesa, Roberto; Bertoglio, Luca
Abstract: OBJECTIVES: The aim of this study was to evaluate the proportion of thoraco-abdominal aortic aneurysms (TAAAs) that could theoretically be treated with the JOTEC ® E-nside ® Thoracoabdominal Branch Endoprosthesis off-the-shelf multibranched endograft. METHODS: Preoperative computed tomography scans of patients with atherosclerotic TAAA treated between 2007 and 2019 were reviewed, and the anatomical feasibility of the E-nside graft was verified by a retrospective study (clinicaltrials.gov: NCT03959670) based on the investigational manufacturer instructions for use. The anatomical factors determining overall feasibility were divided into vascular access (AC) feasibility, aortic (AO) feasibility and visceral vessels (VV) feasibility. RESULTS: Two hundred sixty-eight patients with thoraco-abdominal aneurysms were analysed: the overall treatment feasibility was 43%. AC feasibility was 78%, AO feasibility 60% and VV feasibility 79%. An iliac diameter <8.5 mm excluded 21% of the patients. Aortic feasibility was limited by infrarenal aortic diameter (16%) and size of aortic lumen at the level of visceral vessels (14%). Visceral vessels feasibility was mainly limited by inadequate number (8%) or diameter (12%) of target vessels. Height and orientation of target vessels were adequate in 97% of the cases. Overall feasibility was negatively influenced by female gender (Odds ratio: 3.89; 95% confidence interval 2.03–7.44; P < 0.001): the limiting factors in this subgroup being iliac diameter, infrarenal aortic diameter and visceral vessels diameter. CONCLUSIONS: The E-nside off-the-shelf stent graft can be theoretically employed in almost half of the cases from an all-comers cohort of patients with TAAA. Improvement of device profile and creation of a dedicated infrarenal component are warranted to increase overall feasibility. Female gender significantly affects the overall feasibility. Clinicaltrials.gov: NCT03959670. Abstract : Off-the-shelf multibranched endografts have been developed to circumvent the limitations of the customization process required for fenestrated and branched stent grafts.